UPLC method development and validation for Cefditoren Pivoxil in active pharmaceutical Ingredient - Ram Garg, Navneet Singh, Kona S. Srinivas, Binayak Deb, Ayaz Ahmed (Journal of Applied Pharmaceutical Science)
The objective of the study was to develop UPLC method for the determination of purity of Cefditoren Pivoxil in API and its validation. UPLC is a better technique than HPLC in terms of performance and speed, so it was selected. The method was developed using Acetonitrile and Ammonium Acetate buffer (pH 6.7) and Kromacil column C18 (50×2.1mm, 3.5µ) as a stationary phase at a flow rate of 0.25ml/min. Validation was done by linearity, precision, and robustness studies. The precision was found to be within the limits. The linearity studies indicated the drug obeys Beer’s law and revealed the specified range of linearity for drug was between 80µg/ml and 120µg/ml. The robustness was observed from the insignificant variation in the analysis by changes in flow rate, mobile phase ratio, wavelength, column oven temperature and pH. Forced Degradation study revealed the drug degraded initially by the influence of acid, alkali, and peroxide. Solution stability study showed the drug was not stable for more than 2 h at 25°C but stable at 5°C. It can be concluded that the proposed method was simple, precise, and robust and can be useful for determination of purity of Cefditoren Pivoxil in API by using UPLC.
Keywords: UPLC, Cefditoren Pivoxil, active pharmaceutical ingredient (API), method development, validation.